Cribriform adenocarcinoma of the tongue with cervical lymph nodes involvement: Report of an extremely rare tumor and focus about differential diagnosis with polymorphous adenocarcinoma. Issue 11 (26th November 2021) - De Luca, Pietro; Tassone, Domenico; de Campora, Luca; Simone, Matteo; Marra, Pasquale; Colacurcio, Vito; Costarelli, Leopoldo; Scarpa, Alfonso; Viti, Claudio; Camaioni, Angelo
Abstract: Cribriform adenocarcinoma is a rare tumor that arise in tongue and minor salivary glands. Previously, only 56 case have been described. In this paper, we report a case of a 83‐year‐old man and we focus about the differential diagnosis with polymorphous adenocarcinoma. Abstract : Pre‐operative MRI showed an expansive mass (37 × 33 mm) at the base of the left tongue, involving the body of the tongue, the anterior belly of the digastric muscle, the palatoglossal muscle, and imprinting the homolateral parapharyngeal space.